Kafa’ah in Contemporary Islamic Marriage: Insights from a Systematic and Meta-Analytical Review - Fathullah; Sayehu; Nafan Tarihoran (Islamic Research Publiser, 2025)
The concept of kafa’ah (marital compatibility) in Islamic marriage law has long served as a normative framework to ensure harmony between spouses based on factors such as lineage, wealth, profession, and religious commitment. However, contemporary societies face new realities—such as inter-ethnic marriages, higher levels of education, and socioeconomic diversity—that challenge traditional interpretations of kafa’ah. This study explores how the concept of kafa’ah is interpreted, debated, and applied within contemporary Islamic legal scholarship and systems across Muslim-majority communities. The primary objective is to systematically review the existing literature to identify dominant themes, research gaps, and developments in the application of kafa’ah in contemporary contexts. Using meta-analysis and the PRISMA framework, the researchers selected and analyzed 42 peer-reviewed articles published between 2000 and 2024 from databases including Scopus, ScienceDirect, and PubMed. The findings indicate that most studies on kafa’ah still adopt a normative-theological approach with limited empirical engagement, with the concept most frequently discussed in relation to social status, wealth, piety, and religious affiliation. However, an increasing number of studies reflect a shift in understanding kafa’ah toward mutual respect, shared values, and socioeconomic compatibility rather than rigid class or lineage standards. These findings underscore the necessity of a contemporary, contextual, and reform-oriented approach to kafa’ah, particularly within legal systems and religious fatwas that aim to strike a balance between tradition and social justice, as well as the realities of modern society.